Variation in a range of mTOR-related genes associates with intracranial volume and intellectual disability. Issue 1 (December 2017) - Reijnders, M.; Kousi, M.; Woerden, G.; Klein, M.; Bralten, J.; Mancini, G.; Essen, T.; Proietti-Onori, M.; Smeets, E.; Gastel, M.; Stegmann, A.; Stevens, S.; et al.
Abstract De novo mutations in specific mTOR pathway genes cause brain overgrowth in the context of intellectual disability (ID). By analyzing 101 mMTOR-related genes in a large ID patient cohort and two independent population cohorts, we show that these genes modulate brain growth in health and disease. We report the mTOR activator geneRHEB as an ID gene that is associated with megalencephaly when mutated. Functional testing of mutantRHEB in vertebrate animal models indicates pathway hyperactivation with a concomitant increase in cell and head size, aberrant neuronal migration, and induction of seizures, concordant with the human phenotype. This study reveals that tight control of brain volume is exerted through a large community of mTOR-related genes. Human brain volume can be altered, by either rare disruptive events causing hyperactivation of the pathway, or through the collective effects of common alleles. The mTOR pathway is a key regulator of normal brain development. Here, the authors identify de novo mutations in RHEB, an mTOR activator protein, in patients with intellectual disability associated with megalencephaly and find a role for RHEB in regulating neuronal soma size and migration in vitro and in vivo.